2021
DOI: 10.1371/journal.pone.0255605
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of mask region-based convolutional neural network for the automatic detection and segmentation of abnormal liver density based on hepatocellular carcinoma computed tomography datasets

Abstract: The aim of the study was to use a previously proposed mask region–based convolutional neural network (Mask R-CNN) for automatic abnormal liver density detection and segmentation based on hepatocellular carcinoma (HCC) computed tomography (CT) datasets from a radiological perspective. Training and testing datasets were acquired retrospectively from two hospitals of Taiwan. The training dataset contained 10,130 images of liver tumor densities of 11,258 regions of interest (ROIs). The positive testing dataset con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Sixty studies had lesion segmentation as a primary or secondary study aim. Thirty-six are journal articles [ 24 , 29 , 31 , 32 , 38 , 46 , 47 , 55 , 56 , 62 , 72 , 78 , 84 , 91 , 93 , 94 , 97 , 98 , 102 , 111 , 115 , 117 , 118 , 122 , 124 , 125 , 130 , 133 – 135 , 137 , 138 , 140 , 201 ], and twenty-four [ 22 , 37 , 42 , 64 , 65 , 68 , 82 , 88 , 92 , 96 , 99 , 103 , 108 , 121 , 124 , 126 – 129 , 131 , 132 , 136 , 139 , 200 ] are proceedings papers.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty studies had lesion segmentation as a primary or secondary study aim. Thirty-six are journal articles [ 24 , 29 , 31 , 32 , 38 , 46 , 47 , 55 , 56 , 62 , 72 , 78 , 84 , 91 , 93 , 94 , 97 , 98 , 102 , 111 , 115 , 117 , 118 , 122 , 124 , 125 , 130 , 133 – 135 , 137 , 138 , 140 , 201 ], and twenty-four [ 22 , 37 , 42 , 64 , 65 , 68 , 82 , 88 , 92 , 96 , 99 , 103 , 108 , 121 , 124 , 126 – 129 , 131 , 132 , 136 , 139 , 200 ] are proceedings papers.…”
Section: Resultsmentioning
confidence: 99%
“…Among the selected studies, we found that the mean age of patients across the studies was 56 years, with the study size ranging between 16 [12] and 7512 [13] subjects with HCC. Many of the studies (n=24, 67%) used either Computed Tomography (CT) or Magnetic Resonance Imaging (MRI) scans as the basis of their algorithm development [12][13][14]16,17,[19][20][21][22][23][24][25][28][29][30][31][33][34][35]39,40,[42][43][44]. A modest number of images (100 to 1000) were used for these studies, except for Kim et.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Table 1, 16 studies (44%) were extracted that focused on different AI tools used for the diagnostic purposes of HCC or liver tumors. Many of the studies (n=12, 33%) used CT or MRI scans as the foundation of their technique and developed an AI algorithm to improve various characteristics of the images acquired [12][13][14]16,17,[20][21][22][23][24][25]. Among the studies, the Fully Automated Pipeline based on Machine learning had the highest accuracy of 98.8% for differentiating HCC from normal tissue [18]).…”
Section: Resultsmentioning
confidence: 99%
“…The U-net is a convolutional neural network (CNN) architecture specifically designed for biomedical image segmentation, which also takes into account the spatial context [ 13 ]. CNN architectures such as U-nets have recently shown their value in many medical applications, e.g., in detection, classification, and segmentation tasks based on radiological images [ 28 , 29 ], as they are robust to variations in shape, orientation, and position. Even though the achieved accuracy of 75% of the U-net seems low at first glance, it must be taken into account that this result was achieved with a limited number of samples ( n = 12), a specific marker panel was used, and the calculation of the accuracy is based on the classification of each individual cell.…”
Section: Discussionmentioning
confidence: 99%